CREDIT PERFORMANCE IN BANKING IN INDONESIA DURING 2019-2020 - Wikan Isthika; Amalia Nur Chasanah; Mila Sartika (Jurnal MEBIS (Manajemen dan Bisnis), 2022)
In 2020, the Covid-19 pandemic occurred which affected all sectors of the economy. One of them is the banking industry. This study aims to see how the performance of bank credit in Indonesia was before the pandemic and in the early years of the pandemic. This study uses the variables capital adequacy ratio (CAR), operating costs to operating income (BOPO), return on assets (ROA), and loan to deposits ratio (LDR) in measuring non-performing loans (NPL) or non-performing financing ( NPF). This study uses monthly data from conventional and Islamic banking financial reports for 2019 and 2020. Data testing uses the classical assumption test and multiple linear regression tests. The results of testing the classical assumptions state that the data is feasible for regression testing. Furthermore, the results of the study found that all variables namely CAR, LDR, ROA and BOPO simultaneously affected the NPL or NPF variable. Meanwhile, partially, it was found that CAR and LDR were proven to be able to affect NPL or NPF, while ROA and BOPO had no effect on NPL or NPF in Indonesian banks for the past two years.